Elimination of Discrimination Against Women in Labor Relations and Labor Rights Guarantees - Kasimova Zumrad Rahmatovna (Zien Journals, 2023)
This article analyzes women's rights, elimination of all forms of discrimination of women's rights, improvement of labor legislation regulating women's rights in the field of work, mechanisms to fight against violation of women's rights
Keywords: women's rights; gender inequality; problems of social discrimination; guarantees of women's work, equality between women and men